THE GOOD CONSCIENCE OF CAPITALISM: A READING OF GRAHAM GREENE'S THE QUIET AMERICAN - Pereira, Patrick Araujo; Botoso, Altamir [UNESP] (Centro Univ Uniabeu, 2024)
Henry Graham Greene (1904-1991) was an English writer and the author of over 60 novels. He became renowned for his detective plots, exemplified in books such as The Quiet American (1955) and Our Man in Havana (1958). In The Quiet American , various human dramas unfold, intertwined with broader geopolitical issues emerging in the aftermath of the Second World War. The novel offers a critique of the ideology propagated by North America during its ascent as a global power. A parallel can be drawn between the concept of the good conscience of capitalism as elucidated by French philosopher Jacques Derrida in his seminal work Specters of Marx , and the words and deeds of Greene's protagonists. This article endeavors to elucidate Greene and Derrida's understanding of this good conscience. Additionally, the analysis will draw upon insights from Nietzsche (2012), Fan (2022), and Zizek (1996).
Keywords: conscience; Graham Greene; English literature